2005
DOI: 10.1539/joh.47.424
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality of Industrial Workers Occupationally Exposed to Chromium

Abstract: Semen Quality of Industrial Workers Occupationally Exposed to Chromium: Sunil KUMAR, et al. Reproductive Toxicology and Histochemistry Division, National Institute of Occupational Health (ICMR), India-A total of sixty-one subjects occupationally exposed to chromium in an industry which manufactures chromium sulphate and fifteen control subjects from a nearby industry which does not manufacture any chromium related compounds were studied. The history of each subject was recorded on pre-designed form through int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 24 publications
(28 reference statements)
1
31
1
1
Order By: Relevance
“…Blood chromium positively correlated with the percentage of abnormal sperm in the exposed workers (92). While one study of welders exposed to chromium (VI) reported a 67 % decrease in sperm concentration compared to controls and an inverse correlation between sperm concentration and blood chromium levels in the exposed workers (93), another study showed no signifi cant difference in semen quality between welders and other workers (94).…”
Section: Effects Of Occupational Exposure To Metals On Reproductive Pmentioning
confidence: 98%
“…Blood chromium positively correlated with the percentage of abnormal sperm in the exposed workers (92). While one study of welders exposed to chromium (VI) reported a 67 % decrease in sperm concentration compared to controls and an inverse correlation between sperm concentration and blood chromium levels in the exposed workers (93), another study showed no signifi cant difference in semen quality between welders and other workers (94).…”
Section: Effects Of Occupational Exposure To Metals On Reproductive Pmentioning
confidence: 98%
“…Saxena et al (1990) suggested a risk to growing testes, if rats are exposed to hexavalent chromium during the pre-pubertal stages of their development, which in turn, may disturb normal testicular physiology in adulthood. A significant higher numbers of morphologically abnormal sperm were noticed in a group occupationally exposed to chromium in compare to the unexposed persons, (Kumar et al, 2005).…”
Section: Introductionmentioning
confidence: 86%
“…It also has been reported to have carcinogenic, cytotoxic effects both in human and laboratory animals (Stohs et al, 2001). High levels of chromium in blood, urine and some body tissues are found in workers occupationally exposed to chromium (Kumar et al, 2005). Workers exposed to chromium in welding industry suffered from increased risk of reduced semen quality and sperm abnormalities leading to infertility (Bond, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Other elements such as Cu, Mn, molybdenum (Mo), selenium (Se), and Zn are essential for good health but may be harmful above certain levels (3,8). For example Cr, Mn, and Cu, which act as cofactors for a variety of important enzymes, have been associated with reduced semen quality (9)(10)(11). On the other hand, lower levels of Cu, Se, and Zn may have protective effects on male reproductive outcomes and may assist in counteracting the effects of Cd and Pb (1,4,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%